Photoswitchable transition metal complexes with azobenzene-functionalized imine-based ligands: structural and kinetic analysis. Issue 40 (23rd May 2018) - Markiewicz, G.; Walczak, A.; Perlitius, F.; Piasecka, M.; Harrowfield, J. M.; Stefankiewicz, A. R.
Abstract : We report on the characterization of two imine type ligands containing photoresponsive azobenzene units as side groups and their transition metal ions complexes. Abstract : We report on the characterization of two imine type ligands containing photoresponsive azobenzene units as side groups and their transition metal ions complexes. The ligands, both free and in their complexes undergo trans - > cis photoisomerization after irradiation with UV light, but binding of metal ions reduces both the photoisomerisation reaction rates and cis isomer concentrations in the photostationary states. The greatest diminution in the photoisomerisation rate was observed for the complex containing Cd(ii ), the heaviest among the various transition metal ions tested in this study.